The Application of The “Ludo” Media on The Human Digestive System on Student Learning Outcomes in Elementary Schools - Kartini; Degi Alrinda Agustina; Donna Rhamdan; Weli Susanti (JURNAL ASIMILASI PENDIDIKAN, 2026)
The Ludo game is a teaching tool used in science education. This study aims to explore the effectiveness of using the ludo game in teaching the digestive system to students and its impact on their learning outcomes. The study was conducted in the fifth-grade class at SDN 005 Tarakan. It employed a one-group pretest-posttest design, with data analyzed using a t-test. The researcher administered a pretest before the instructional activities began. After the implementation of the Ludo game was completed, a posttest was administered at the end of the learning process. The result showed a significant difference between the pretest and posttest scores for the digestive system Ludo game, as well as an excellent student response with a score of 82.08. the game encourage student to compete and collaborate in achieving learning objectivies simultaneously.